AB0891 Long-Term Cumulative Organ Damage Assessment in A Cohort of Patients with Juvenile Dermatomyositis. (10th June 2014) - Quesada-Masachs, E.; Díaz-Mendoza, C.; Άvila-Pedretti, G.; Simeon-Aznar, C.-P.; Selva-O'Callaghan, A.; Modesto, C.
Abstract : Objectives: To assess cumulative organ damage in juvenile dermatomyositis (JDM) patients after long term disease and to establish the possible relationship between the final damage score and the treatment received during the first year of disease. Methods: A retrospective study was conducted in a cohort of patients with JDM followed in a Unit of Pediatric Rheumatology from December 1985 to October 2013. The cumulative organ damage was evaluated using the Myositis Damage Index (MDI), a score which assesses the presence of damage in 11 organs/systems (minimal score value 0- maximum 38). This score includes two variants: the cumulative MDI score which covers all damage present for at least 6 months during the entire disease course and the actual MDI score which measures the damage that is clinically detectable at the time of the visit. A physician visual analogue scale (VAS) (0-10 cm) was used to assess the severity of total damage at last follow-up. Data regarding the received treatment was recorded. Results: The sample included 16 patients, 8 females and 8 males. The mean age at diagnosis was 7.68 years (range 2.75-14.4). The mean time of follow-up since disease onset was 11 years (range 1.2-28). Patients who received disease modifying anti-rheumatic drugs (DMARD) biological or not biological during the first year of JDM course were considered as "aggressively" treated (n=11), while patients who didn't receive immunomodulatory drugs during the first year were considered as "non aggressively" treated (N=5). Data referred to extension and severity of damage is recorded in table 1 (see below). MDI score after 1 year of follow-up, cumulative MDI and actual MDI measured at last follow-up as well as the physician assessment of the severity of total damage (VAS) are expressed as mean and range. The systems more frequently involved were: skin (87.5%), muscular (87.5%), endocrine (43.75%) and skeletal (25%). Conclusions: Data obtained suggests that in JDM intensification of treatment during the first year after disease onset could be a factor that determines the total cumulative damage to the same extent as the clinical course. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4398